2000
DOI: 10.1177/107110070002100110
|View full text |Cite
|
Sign up to set email alerts
|

Growth Disturbances After Distal Tibial Physeal Fractures

Abstract: Twenty-four patients with distal tibial growth disturbance were reviewed. Disturbances were classified as physeal bar (prior to deformity), angular, linear or combined deformities. Treatment consisted of osteotomy in fourteen, epiphyseodesis in seven, excision of bony bar in two, and observation in one patient. Follow up was an average 36.6 months (range 4-129 months) after treatment of growth disturbance. The age at time of injury was 10.4 years of age average (range 3-15 years). There were 12 SH2, 2 SH3, 7 S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0
1

Year Published

2006
2006
2022
2022

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(18 citation statements)
references
References 25 publications
0
17
0
1
Order By: Relevance
“…shoe lifts, excision of the bone bridge, leg lengthening, contra and ipsilateral epiphysiodesis, corrective osteotomies [9,10].…”
Section: Introductionmentioning
confidence: 99%
“…shoe lifts, excision of the bone bridge, leg lengthening, contra and ipsilateral epiphysiodesis, corrective osteotomies [9,10].…”
Section: Introductionmentioning
confidence: 99%
“…Kling et al [20] described leg length discrepancies of up to 4 cm in patients who were 11 years or older at the time of injury. Furthermore, Berson and coworkers [2] found that axial deviations are more frequent, the later the growth arrest appears. In contrast, leg length differences are assumed to be equally frequent, no matter whether the growth disturbance occurs early (up to 6 months) or late after the injury.…”
Section: Restrictive Growth Disturbances: Incidence and Consequencesmentioning
confidence: 99%
“…47 On CT, if there is > 2 mm of displacement after attempted closed reduction, operative treatment is in-dicated to avoid posttraumatic osteoarthritis or growth disturbance. 49,50 Of note, extra-articular triplane fractures do not require anatomical reduction because they do not violate the ankle joint. 49…”
Section: Triplane Fracturesmentioning
confidence: 99%